Validation of the Hospital Ethical Climate Survey for older people care - Suhonen, Riitta A.; Stolt, Minna; Katajisto, Jouko K.; Charalambous, Andreas; Olson, Linda L. (My University, 2015)
Background: The exploration of the ethical climate in the care settings for older people is highlighted in the literature, and it has been associated with various aspects of clinical practice and nurses’ jobs. However, ethical climate is seldom studied in the older people care context. Valid, reliable, feasible measures are needed for the measurement of ethical climate. Objectives: This study aimed to test the reliability, validity, and sensitivity of the Hospital Ethical Climate Survey in healthcare settings for older people. Design: A non-experimental cross-sectional study design was employed, and a survey using questionnaires, including the Hospital Ethical Climate Survey was used for data collection. Data were analyzed using descriptive statistics, inferential statistics, and multivariable methods. Participants and research context: Survey data were collected from a sample of nurses working in the care settings for older people in Finland (N = 1513, n = 874, response rate = 58%) in 2011. Ethical considerations: This study was conducted according to good scientific inquiry guidelines, and ethical approval was obtained from the university ethics committee. Results: The mean score for the Hospital Ethical Climate Survey total was 3.85 (standard deviation = 0.56). Cronbach’s alpha was 0.92. Principal component analysis provided evidence for factorial validity. LISREL provided evidence for construct validity based on goodness-of-fit statistics. Pearson’s correlations of 0.68–0.90 were found between the sub-scales and the Hospital Ethical Climate Survey. Discussion: The Hospital Ethical Climate Survey was found able to reveal discrimination across care settings and proved to be a valid and reliable tool for measuring ethical climate in care settings for older people and sensitive enough to reveal variations across various clinical settings. Conclusion: The Finnish version of the Hospital Ethical Climate Survey, used mainly in the hospital settings previously, proved to be a valid instrument to be used in the care settings for older people. Further studies are due to analyze the factor structure and some items of the Hospital Ethical Climate Survey.
Keywords: Care settings for older people; Ethical climate; Instrument; Validity; Work environment